2020
DOI: 10.1038/s41746-020-0236-4
|View full text |Cite
|
Sign up to set email alerts
|

Secondary care provider attitudes towards patient generated health data from smartwatches

Abstract: Wearable devices, like smartwatches, are increasingly used for tracking physical activity, community mobility, and monitoring symptoms. Data generated from smartwatches (PGHD_SW) is a form of patient-generated health data, which can benefit providers by supplying frequent temporal information about patients. The goal of this study was to understand providers' perceptions towards PGHD_SW adoption and its integration with electronic medical records. In-depth, semi-structured qualitative interviews were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…Improvements to the interface should prioritize allowing participants more control over data for better customization as per specific user needs. Results from this usability study support the findings from our qualitative interviews [ 3 ] as well as other studies in which health care professionals trusted health data from smartwatches and believed those would be helpful in clinical decision making [ 19 ]. Previous studies found that health care providers believed that wearable devices could improve health [ 20 ] and recommended health data from smartwatches to be incorporated into the convenient and secure environment of EHR systems [ 3 ].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Improvements to the interface should prioritize allowing participants more control over data for better customization as per specific user needs. Results from this usability study support the findings from our qualitative interviews [ 3 ] as well as other studies in which health care professionals trusted health data from smartwatches and believed those would be helpful in clinical decision making [ 19 ]. Previous studies found that health care providers believed that wearable devices could improve health [ 20 ] and recommended health data from smartwatches to be incorporated into the convenient and secure environment of EHR systems [ 3 ].…”
Section: Discussionsupporting
confidence: 87%
“…Results from this usability study support the findings from our qualitative interviews [ 3 ] as well as other studies in which health care professionals trusted health data from smartwatches and believed those would be helpful in clinical decision making [ 19 ]. Previous studies found that health care providers believed that wearable devices could improve health [ 20 ] and recommended health data from smartwatches to be incorporated into the convenient and secure environment of EHR systems [ 3 ]. Our qualitative study [ 3 ] also found that each medical specialty required different types of data and applied those data to different uses.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations